Decision support systems for business intelligence - Sauter, Vicki Lynn, 1955-; Sauter, Vicki Lynn, 1955- (Hoboken, N.J. : Wiley, 2010)
"This book examines decision making in general, the translation of knowledge about decision making into a DSS model, and the actual programming of a DSS. In addition, it combines the theoretical underpinnings of the topic with practical application using tools and technology currently available. Topics are discussed on three levels: general theory, implications for DSS design, and code development. This approach provides readers with practical examples than can be adopted into systems design. The Second Edition has been completely updated to reflect new technologies as well as the demands upon technology that have evolved since the publication of the First Edition in 1996. The book utilizes a combination of Dreamweaver and Cold Fusion, which are both popular software products that follow industry standards. (The First Edition utilized Level 5 Object, but all references to the software have been removed as it is not deemed a viable tool any longer.) In light of the numerous advances in the field of DSS over the years, there are many topics throughout the book that have updated and revised. For example, data warehousing has increased substantially in importance since the First Edition, and this section has been completely revised. The topic of business intelligence has been added, and similarly, data mining coverage has been increased via additional discussion and examples. In addition, transnational corporations have become more prevalent and are addressed accordingly"--
"Decision support systems are a of computer-based information systems including knowledge based systems that support decision making activities. Since there are many approaches to decision-making as well as a wide range of domains in which decisions are made, the concept of decision support system (DSS) is very broad. A DSS can take many different forms. Supporting a decision means helping people working alone or in a group gather intelligence, generate alternatives, and make choices. Supporting the choice making process involves supporting the estimation and the evaluation and/or the comparison of alternatives"--
(3SjO GdJhfSi (B/ (3cdjI fXe GdeYdheGJ hYdhe GdMGSHs
Rev. ed. of: Decision support systems. 1997.
Includes bibliographical references and index.
Keywords: Decision support systems; Decision making